Prescribing peritoneal dialysis and achieving good quality dialysis in low and low-middle income countries. Issue 3 (May 2020) - Liew, Adrian
The provision of long-term renal replacement therapies for patients with end-stage kidney disease (ESKD) in low and low-middle income countries (LLMICs) has been a pervasive challenge, impeded mainly by monetary constraints, limited health-care resources, and geographical and logistic difficulties. Even for patients who could initiate dialysis, discontinuation of dialysis treatment due to the lack of financial sustainability is a valid concern. While the delivery of high-quality dialysis should not be compromised in these settings, perpetuity on dialysis is of paramount consideration for these patients, with sustaining life being just as important as achieving clinical well-being. As intensification of peritoneal dialysis (PD) prescription comes with immense cost in these settings, the strategy for stretching affordability of dialysis involves optimizing the number of PD exchanges required or delaying the transition to a high PD dose of four bags per day of continuous ambulatory PD (CAPD) prescription. This can be accomplished through the use of low-cost adjunctive treatment, by preserving residual kidney function and adopting incremental PD. The use of expensive, complex, or inaccessible monitoring tools for peritoneal membrane function and dialysis clearance could be replaced by clinical assessment and widely available biochemical indicators, which will significantly reduce the investigation costs, with consequent savings that could allow for lengthening the duration of PD therapy. Finally, it is important for each PD program in LLMICs to monitor these outcome indicators, to ensure the consistent delivery of acceptable quality of PD to their patients.